Dissociable roles of dopamine within the core and medial shell of the nucleus accumbens in memory for objects and place - Nelson, Andrew J.D.; Thur, Karen E.; Marsden, Charles A.; Cassaday, Helen J. (American Psychological Association, 2010)
There is increasing focus on the role of the nucleus accumbens (NAc) in learning and memory, but there is little consensus as to how the core and medial shell subregions of the NAc contribute to these processes. In the current experiments, we used spontaneous object recognition to test rats with 6-hydroxydopamine lesions targeted at the core or medial shell of the NAc on a familiarity discrimination task and a location discrimination task. In the object recognition variant, control animals were able to discriminate the novel object at both 24-hr and 5-min delay. However, in the lesion groups, performance was systematically related to dopamine (DA) levels in the core but not the shell. In the location recognition task, sham-operated animals readily detected the object displacement at test. In the lesion groups, performance impairment was systematically related to DA levels in the shell but not the core. These results suggest that dopamine function within distinct subregions of the NAc plays dissociable roles in the modulation of memory for objects and place.